Vertical specialisation and gains from trade. (21st November 2020) - Alexander, Patrick
Abstract: Multi‐stage production is a significant source of gains from trade in many recent quantitative trade models. Meanwhile, specialisation across stages of production, or 'vertical specialisation', has been largely ignored in these models. In this paper, I provide evidence that vertical specialisation is a salient feature in the international trade data, which suggests that standard models are inaccurate. I develop a model with multi‐stage production where country‐level productivity differences provide a basis for vertical specialisation and potentially new gains from trade. I then quantify the gains from vertical specialisation according to the model using data. Despite the evidence of vertical specialisation in the data, I find that the average gains from trade due to this channel are modest at less than 1% of GDP. These results suggest that, if vertical specialisation is an important source of gains from trade, then revealing these gains may require either more complex models, or more granular data, than are typically used in workhorse quantitative trade models.